2022
DOI: 10.14348/molcells.2021.0211
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast Cell Subtypes and Dysfunction in the Placenta of Individuals with Preeclampsia Revealed by Single-Cell RNA Sequencing

Abstract: Trophoblasts, important functional cells in the placenta, play a critical role in maintaining placental function. The heterogeneity of trophoblasts has been reported, but little is known about the trophoblast subtypes and distinctive functions during preeclampsia (PE). In this study, we aimed to gain insight into the cell type-specific transcriptomic changes by performing unbiased single-cell RNA sequencing (scRNA-seq) of placental tissue samples, including those of patients diagnosed with PE and matched healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 45 publications
0
18
0
5
Order By: Relevance
“…For example, EIF4E in the C6 cluster is involved in protein synthesis and a key checkpoint in the control of the rate of mRNA translation [ 55 ], and EIF4E has a critical role in the pathology of various types of cancer [ 56 , 57 ]. Consistent with these findings, it has been recently shown that the genes with upregulated expression in extravillous trophoblast (EVT) were involved in translation by using single-cell RNA sequencing [ 51 ]. In contrast, we observed that PS genes were mainly enriched in the cyan-associated C3 and C5 clusters.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, EIF4E in the C6 cluster is involved in protein synthesis and a key checkpoint in the control of the rate of mRNA translation [ 55 ], and EIF4E has a critical role in the pathology of various types of cancer [ 56 , 57 ]. Consistent with these findings, it has been recently shown that the genes with upregulated expression in extravillous trophoblast (EVT) were involved in translation by using single-cell RNA sequencing [ 51 ]. In contrast, we observed that PS genes were mainly enriched in the cyan-associated C3 and C5 clusters.…”
Section: Discussionmentioning
confidence: 64%
“…It was also reported that hypoxia, ischemia, and the production of proinflammatory cytokines associated with PE lead to protein misfolding and initiate endoplasmic reticulum (ER) stress [ 48 , 49 , 50 ]. Furthermore, Zhou et al recently showed that the genes with upregulated expression in syncytiotrophoblast (SCT) were involved in protein folding by using single-cell RNA sequencing [ 51 ]. These observations suggest that cyan and magenta module genes are related to some extent to the functions that regulate protein processing and folding, and thus these genes may contribute to the PE risk during placenta development and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…The 10X genomics Chromium platform builds on the Gem Code technology, which has been frequently used for Single cell transcriptome research in human placenta and decidua ( Vento-Tormo et al, 2018 ; Wang et al, 2021a ; Du et al, 2021 ; Huang et al, 2021 ; Yang et al, 2021 ; Zhou et al, 2022a ). The core of the technology is a Gel bead in Emulsion (GEM) ( Zheng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… Zhang et al (2021) revealed the difference between the preeclampsia and healthy pregnancy groups by analyzing the transcripts of 11,518 cells at the single cell level and found that GO terms enriched in EVT from patients with preeclampsia were mainly associated with immune responses, suggesting altered placental immune function in preeclampsia. Zhou et al (2022b) classified EVT into four subtypes and found that pro-inflammatory, immune, and oxidative stress-related pathways in preeclampsia EVT subtypes were activated. Further analysis revealed that the transcription factors CEBPB, ATF3 , and GTF2B were significantly reduced in expression in preeclamptic EVT, and CEBPB and GTF2B were selected for the next functional study, which revealed that knockdown of these two molecules significantly reduced cell viability and invasiveness, and were hypothesized to be involved in the pathogenesis of Pre-eclampsia ( Zhou et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation